Computational fluid dynamics simulation of internally circulating fluidized bed reactor for dry reforming of methane. (April 2022) - Thiemsakul, Dulyapat; Kamsuwan, Chaiyanan; Piemjaiswang, Ratchanon; Piumsomboon, Pornpote; Chalermsinsuwan, Benjapon
Abstract: Internally circulating fluidized bed reactor (ICFB) is the reactor that combines the conventional circulating fluidized bed (CFB) reactor system, including riser, downer, loop seal and cyclones, into a single compact reactor column. The ICFB reactor column is separated into two sections (riser and downer) by baffles and is linked together via connecting ports. The solid particles are circulated in the ICFB reactor by unequal fluidizing velocities in the riser and downer sections. The solid particles in the downer section are operated with low fluidizing velocity in the bubbling fluidization regime. In the riser section, the solid particles are transferred to the downer section because of the high fluidizing velocity. In this study, the carbon dioxide reforming or dry reforming reaction of methane was investigated. Dry reforming is a reaction between carbon dioxide and methane, which are the major greenhouse gases, for producing syngas, hydrogen and carbon monoxide. The hydrodynamics and dry reforming reaction with different reactor designs were explored using two-dimensional Eulerian–Eulerian computational fluid dynamics simulation (CFD). The ICFB reactor with no elevation gas distributor, 90 cm of draft tube height, 2 cm of loop-seal length and 1 cm of gas outlet diameter gave the highest methane conversion of 15.4%. The analysis of variance (ANOVA) indicated that the length of loop-seal and the gas outlet diameter gave substantial negative and positive effects on methane conversion, respectively. The interaction between length of loop-seal and gas outlet diameter also had a significant effect on the methane conversion. Although the ICFB reactor in this study gave the methane conversion slightly lower than referenced literature conventional CFB reactor, the ICFB reactor is the reactor that can reduce construction cost and simplify complex reactor operation.